Analysis of constitutional court decision number 62/PUU XXII/2024 concerning the elimination of the minimum threshold for presidential nominations from a siyasah qadaiyyah perspective - Munawar, M Ramdan; Saebani, Beni Ahmad; Prasetyo, Ridwan Eko (FISIP UIN SGD Bandung, 2025)
This study examines Constitutional Court Decision Number 62/PUU-XXII/2024, which annulled the presidential candidacy threshold in Article 222 of Law No. 7/2017 for violating principles of morality, rationality, and justice. Using a normative juridical approach and the siyasah qadaiyyah (Islamic judicial political theory) perspective—alongside Rousseau’s concept of popular sovereignty—this research analyzes the decision’s legal reasoning and its impacts on Indonesia’s constitutional system, governance, and institutional balance. The findings show that removing the threshold enhances democratic participation but may also lead to political instability and institutional imbalances. The study recommends strengthening deliberation, oversight, and justice in political processes, guided by the siyasah qadaiyyah approach, to achieve a just and stable constitutional order. Contribution: This research not only enriches academic understanding but also provides guidance for policymakers working to ensure that Indonesia’s constitutional evolution upholds both justice and stability.